Hadith #4032 - Sahih al-Bukhari - Abu 'Imran al-Ansari al-Shami أبو عمران الأنصاري الشامي (Sahih al-Bukhari)
Anas looked at the people wearing Tailsans (i.e. a special kind of head covering worn by Jews in old days). On that Anas said, “At this moment they (i.e. those people) look like the Jews of Khaibar.”
Grade: Sahih

Hadith #6614 - Sahih Muslim - Abu 'Imran al-Ansari al-Shami أبو عمران الأنصاري الشامي (Sahih Muslim)
Recite the Qur’an. The rest of the hadith is the same.
Grade: Sahih

Hadith #3873 - Sunan Abi Dawud - Abu 'Imran al-Ansari al-Shami أبو عمران الأنصاري الشامي; Abu al-Darda; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin ''Aabadh محمد بن عبادة; Tha'lbah bin Muslim al-Khth'my ثعلبة بن مسلم الخثعمي الشامي; Umm al-Darda'a أم الدرداء; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
Wa’il said: Tariq ibn Suwayd or Suwayd ibn Tariq asked the Prophet (ﷺ) about wine, but he forbade it. He again asked him, but he forbade him. He said to him: Prophet of Allah, it is a medicine. The Prophet (ﷺ) said: No it is a disease.
Grade: Sahih